Stability of the Solution Sets of Parametric Generalized Quasiequilibrium Problems - Nguyen, Van Hung (H. : ĐHQGHN, 2017)
In this paper we establish sufficient conditions for the solution mappings of parametric generalized vector quasiequilibrium problems to have the stability properties such as lower semicontinuity, upper semicontinuity, Hausdorff lower semicontinuity, continuity, Hausdorff continuity and closedness. The results presented in the paper improve and extend the main results of Kimura-Yao [J. Global Optim. 138, (2008) 429-- 443], Kimura-Yao [Taiwanese J. Math., 12, (2008) 649--669] and Anh-Khanh [J. Math. Anal. Appl., 294, (2004) 699--711]. Some examples are given to illustrate our results.